2017
DOI: 10.1080/17518423.2017.1282052
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcome and quality of life following childhood stroke – A systematic review

Abstract: Objectives. The aim of this paper was to critically review the recent literature on psychosocial and behavioural outcome following childhood stroke, to assess whether quality of life is affected and to investigate the factors related to psychosocial outcome.Methods. Literature searches were conducted and identified 36 relevant papers from the period 1908-2016.Results. The systematic review found that many children experience difficulties in a wide range of psychosocial domains. Quality of life can also be sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…In line with these findings, researchers have uncovered similar needs in their samples, ranging from requiring help in class to placement in a special education program (De Schryver et al, 2000;Ganesan et al, 2000). In fact, a recent systematic review examining psychosocial outcome after childhood stroke calculated that, across 36 studies, approximately half of patients required extra educational help (O'Keeffe et al, 2017). Although our results highlight academic struggles, they also illustrate a positive finding: that youth are receiving assistance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with these findings, researchers have uncovered similar needs in their samples, ranging from requiring help in class to placement in a special education program (De Schryver et al, 2000;Ganesan et al, 2000). In fact, a recent systematic review examining psychosocial outcome after childhood stroke calculated that, across 36 studies, approximately half of patients required extra educational help (O'Keeffe et al, 2017). Although our results highlight academic struggles, they also illustrate a positive finding: that youth are receiving assistance.…”
Section: Discussionsupporting
confidence: 77%
“…Analyses of differences in school-related quality of life, as reported by youth and parents separately, indicated that youth with and without stroke seem to experience similar levels of satisfaction with their school environment, peer support, and social acceptance. Hypotheses had posited significant differences based on the literature; namely, a recent systematic review concluded that childhood stroke significantly affects quality of life, including domains relating to school (O'Keeffe et al, 2017). Although negative outcomes in quality of life were consistently found in the literature, some studies have focused on positive outcomes after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Patients with stroke bring about physical, psychological, social and economic burdens, and health related quality of life (QOL) of the patients are low. [68]…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on healthy behaviors and quality of life and their determinants offers additional insights into what factors are associated with well-being after ABI such as stroke, brain tumors, and TBI (e.g., Di Battista et al, 2014;Gupta & Jalali, 2017;O'Keeffe et al, 2017). For example, health promotion and self-efficacy have been shown to be positively associated with health status, life satisfaction, and participation after TBI (Braden et al, 2012).…”
Section: Introductionmentioning
confidence: 99%